Motivating Mentally Retarded Students by Using the Quizizz Application - Tosi Rut Syamsun; John Pahamzah; Syafrizal Syafrizal (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2023)
The purpose of this study was to investigate why students in a special needs school who are mentally retarded use the Quizizz application and how teachers utilize the program at special needs school (Sekolah Khusus) 01 Serang city. Case studies made up the research methodology. The instructor and mentally retarded students, a ninth-grade mentally disabled student at Sekolah Khusus Negeri 01 Kota Serang, were watched and interviewed by the researcher. According to the research's results, utilizing Quizizz in the special needs school (SKh) 01 in Serang city began with the instructor introducing or chatting with the ninth-graders about it in order for them to feel more at test using the online assessment technique. The teacher employed Quizizzes extremely useful features in the Quizizz implementation as well. The responses of students toward using Quizizz were based on an interview with mentally retarded students, which revealed that: (1) The majority of students agree that Quizizz is excited motivation, and fun and that Quizizz creates an engaging atmosphere; (2) Quizizz is interesting with lots of useful features; and (3) A competitive surroundings can be created because Quizizz has many difficult features, which encourages the students to be the top scorer on the Quizizz leaderboard. Mentally disabled pupils in English language instruction may benefit from the Quizizz application.